STATISTICAL ANALYSIS OF ASSESSMENT OF THE VOLUME OF THE HIDDEN ECONOMY IN THE REPUBLIC OF UZBEKISTAN - Irismatov, Xumoyunmirza (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2023)
This article examines the content and state of the hidden economy in our country, statistical methods used to assess its size. Measures to reduce the share of the hidden economy in our country as much as possible are also explained.